Analisis Filogenetik Burung Maleo (Macrocephalon maleo) Berdasarkan Sekuen Intron Satu Gen Rhodopsin (RDP1) Nukleus - I Made Budiarsa; I Wayan Tunas Artama; Langkah Sembiring; Jesmandt Situmorang (Universitas Atma Jaya Yogyakarta, 2010)
The phylogenetic relationships of the maleo (Macrocephalon maleo) were analyzed based on thefirst intron of rhodopsin nuclear gene sequence data obtained from 15 individuals, along withthose of 22 individuals taken from GenBank. The phylogenetic trees were reconstructed byNeighbor-Joining (NJ) method. Results indicated that 956 bp of RDP1 sequence, 414 (43.4%)sites were variable and 317 (33.2%) sites were phylogenetically-informative. The basecomposition for all species analyzed in this research were as follows: T 25.3%, C 26.3%, A18.5%, and G 29.9%. Analysis of RDP1 sequence produced trees that were remarkably wellresolved and had topologies at the marga level. The phylogenetic analysis showed that maleowas monophyly of Macrocephalon and closely related to Aepypodius, Talegalla, Leipoa andAlectura.